First country-wide survey of the Endangered Asian elephant: towards better conservation and management in Sri Lanka - Fernando, Prithiviraj; De Silva, M.K. Channa R.; Jayasinghe, L.K.A.; Janaka, H.K.; Pastorini, Jennifer (Oryx, 2021)
The Endangered Asian elephant Elephas maximus comes into widespread conflict with agrarian communities, necessitating active management. The species’ distribution is of primary importance for management planning. However, data-based countrywide distribution maps have not been available for any of the 13 Asian elephant range states. We conducted a 5 × 5 km grid-based questionnaire survey in Sri Lanka to produce an island-wide elephant distribution map. Elephants occur over 59.9% of Sri Lanka and people are resident in 69.4% of elephant range, indicating the challenge of separating people and elephants at a landscape scale. Elephants in Sri Lanka have lost 16.1% of their range since 1960 but their current distribution remains largely contiguous. We found the range of adult males was 15.1% greater, and less seasonal, than that of herds, possibly because males have a higher tolerance for conflict with people. The distribution of conflict coincided with the co-occurrence of humans and elephants. We conclude that a human–elephant coexistence model is the only viable option for effectively mitigating human–elephant conflict and conserving elephants in Sri Lanka. The findings are currently being used to effect a paradigm change in elephant conservation and management in the country.